Unlived Lives, Imaginary Widowhood and Elizabeth Bowen's A World of Love. (4th August 2020) - Bryan, Rachel
Abstract: This article reads Elizabeth Bowen's 1955 novel A World of Love as exploring the legacy of certain highly imaginative coping mechanisms that were adopted by women in response to wartime losses. Acknowledging how Bowen's mid-century works exhibit a curious return to the lot of those who came of age amidst the demographic imbalances that followed the Great War, it suggests that A World of Love interrogates the psychological draw of 'imaginary widowhood': a form of counterfactual self-fashioning that saw many single women of Bowen's generation elect to view themselves not as spinsters, but as those who would have been married were it not for the conflict. Noting parallels between the novel's depiction of a girl whose sexuality is awakened by the letters of a long-dead soldier from the Great War and the various forms of appropriation that were encouraged around the body of the Unknown Warrior—including the 1918 literary hoax The Love of an Unknown Soldier: Love Letters Found in a Trench —the article offers a new account of A World of Love as a text which registers the ambivalent and creatively rich qualities of a psychological climate that was at work throughout the twentieth century. Bowen's novel, it argues, is propelled by a profound interest in the forces which induced successive generations of British women to forge intimate counterfactual relationships with those lives rendered unliveable, and the loves that were denied them, on account of world war.